Tradisi Bersih Desa Putukrejo Nganjuk Jawa Timur melalui Kearifan Lokal Wayang Timplong - Sri Martini (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2023)
This study aims to examine the Timplong Puppet Show in the Clean Village Tradition in Putukrejo Village, Nganjuk, East Java,. Wayang Timplong is a traditional art from Nganjuk, East Java. Puppet Timplong has a uniqueness including; made of wood that is inlaid until it is flat with sculptures to form faces and other ornaments that are colored. The Wayang Timplong show does not require a shadow because the shape of the puppet is clearly defined so that the puppet show can be held in the morning, afternoon, afternoon or evening. Wayang Timplong in its heyday was commonly used by the public in various events including; weddings, circumcisions, thanksgiving, village clean traditions, ruwatan and nandar. Along with the development of the Wayang Timplong era, the community began to abandon it and until now only certain events still survive using the Timplong Puppet such as; the clean tradition of the village, ruwatan and nandar because it is related to community beliefs passed down by ancestors through a tradition that the Timplong Puppet is able to ward off all kinds of disasters in a village. Wayang Timplong contains the values ​​of life and character education which are depicted through stories with the theme of Panji.